Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat Yang Dilayani Pada Kantor Kecamatan Sungai Aur Kabupaten Pasaman Barat - Hilmasih Fahmi; Sri Arita (Universitas Negeri Padang, 2023)
The purpose of this study is to determine the impact of service quality on customer satisfaction at the Sungai Aur sub-district office in West Pasaman Regency. This service’s quality is measured across five dimensions: responsiveness, dependability, emphaty, and assurance. This is a quantitative study that employs multiple linear regression methods with the SPSS version 22 program. The population in this study is all the people of Sungai Aur sub-district who have come and received services, with a sample of 92 people drawn using the Slovin formula with purposive sampling in this study. A questionnaire was used to collect data.Validity and reliability tests are used in the research instrument test. At the data analysis stage, descriptive and inductive analysis were performed. Normality test, multicolinearity test, heteroscedasiticity test, and multiple reggresion analysis are examples of inductive analysis. The F test is used to test the hypothesis and the coefficient of determination (R2). The findings of this study show that the five services quality variables, namely responsiveness, reliability, emphaty, tangibles, and assurance have a significant and positive effet on the satisfaction of people served at the Sungai Aur District Office in West Pasaman Regency.